Acute Aneurismal Bilateral Subdural Haematoma without Subarachnoid Haemorrhage: A Case Report and Review of the Literature - Ossama Mansour; Tamer Hassen; Sameh Fathy (Case Reports in Neurological Medicine)
Spontaneous pure acute bilateral subdural haematoma (ASDH) without intraparenchymal or subarachnoid haemorrhage caused by a ruptured cerebral aneurysm is extremely rare. It can follow rupture of different aneurysms specially located in anterior incisural space; the most frequently encountered location is the PcoA aneurysms as demonstrated in the present case. We present a case report of a PcoA aneurysm presenting as pure bilateral ASDH. A high level of suspicion for bleeding of arterial origin should be maintained in all cases of acute subdural haematoma without history of trauma. The neurological status on admission dictates the appropriate timing and methodology of the neuroradiological investigations.